The identification of a novel lead class for phosphodiesterase 2 inhibition by fragment-based drug design. Issue 23 (1st December 2017) - Forster, Ashley B.; Abeywickrema, Pravien; Bunda, Jaime; Cox, Christopher D.; Cabalu, Tamara D.; Egbertson, Melissa; Fay, John; Getty, Krista; Hall, Dawn; Kornienko, Maria; Lu, Jun; Parthasarathy, Gopal; et al.
Graphical abstract: Abstract: We have identified a novel PDE2 inhibitor series using fragment-based screening. Pyrazolopyrimidine fragment 1, while possessing weak potency (Ki  = 22.4 μM), exhibited good binding efficiencies (LBE = 0.49, LLE = 4.48) to serve as a start for structure-based drug design. With the assistance of molecular modeling and X-ray crystallography, this fragment was developed into a series of potent PDE2 inhibitors with good physicochemical properties. Compound 16, a PDE2 selective inhibitor, was identified that exhibited favorable rat pharmacokinetic properties.